ANALISIS FAKTOR YANG MENENTUKAN MINAT BELI KONSUMEN TERHADAP E-COMMERCE FASHION DI KOTA PALEMBANG - prili sinta prastiwi; zakaria wahab; welly nailis (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2017)
This research aim to know the factor analysis of the factors wich determine the consumer buying towards the e-commerce fashion. The attributes in this research were the quality of statisfied products (X1.01), the variety types of products (X1.02), having good brand image (X1.03), the products customized with the lates model (X1.04), the product display looks interesting on the websites (X1.05), the product description is obvisious and convincing (X1.06), the products can be orderer easily (X1.07), the costs is same as in departement store (X1.08), affordable by the consumers (X1.09), there is discount or free shiping (X1.10), easy acces of the website (X1.11), easy acces of the reservation items (X1.12), an extensive distribution network of e-commerce fashion (X1.13), a good website display (X1.14), easy verification of payments (X1.15), interesting brand ambassador (X1.16), interesting advertisment (X1.17), the promotion is often aired in the printed and electronic media (X1.18), the promotion of free shipping the items (X1.19), there are many monthly and special promotions (X1.20). The thecniques analysis that was used in this research was factor analysis, the result of the analysis done into 20 attributes showed that there were four variables including; quality, accessibility and service (X1), brand and product display (X2), promotion (X3), prices and discount (X.4). Keyword: Buying interest, E-commerce fashion, Factor analysis